Osobennosti pitanija sportsmenov-stajerov v cikliceskich vidach sport - Kašapov, R. I.; Kašapov, R. R. (Voprosy pitaniia, 2019)
The number of different endurance sporting events is increasing annually. In the general population the number of participants in such competitions as marathon running, road racing, open water swimming and triathlon is growing. In this regard, much attention is paid to the scientific study of various aspects of nutrition as a factor in energy synthesis in muscle tissues during prolonged physical activity. The review summarizes an analysis of the nutritional data of athletes of various sports who have a long and extra-long physical activity. Information on the role of energy macronutrients (carbohydrates and fats) in the biochemical processes in the organism of athletes during long-term training and competition activities is given. The effectiveness of their consumption to improve performance in cyclic sports during prolonged exercise is analyzed. Various options for using certain compositions to improve endurance indicators, as well as possible undesirable consequences of the use of some nutrients by athletes-styers, are considered in the article.